2002
DOI: 10.1021/jf020120l
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Foliar Polyphenolic Composition in Sweetpotato (Ipomoea batatas L.) Genotypes

Abstract: Trials over two years were conducted using 1389 sweetpotato (Ipomoea batatas L.) genotypes collected from all over the world to characterize the polyphenolic composition in sweetpotato leaves. Wide variation was observed in relation to their total and individual leaf polyphenolic constituents. In all genotypes studied, the total polyphenol contents of sweetpotato leaf ranged from 1.42 to 17.1 g/100 g dry weight. The six different polyphenolic compounds were identified and quantified by NMR, FABMS, and RPHPLC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
178
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(200 citation statements)
references
References 28 publications
18
178
2
2
Order By: Relevance
“…Thus the structure of six fractions obtained was identified by UV, 1 H-NMR and 13 C-NMR spectra by comparision with an authentic sample or the reported compound. 27,28) Statistical Analyses Data were expressed as the meanϮ S.D. The significance of difference was evaluated using Student's t-test 29) and pϽ0.05 was taken as significant.…”
Section: Isolation and Identification Of Antioxidant Componentsmentioning
confidence: 99%
“…Thus the structure of six fractions obtained was identified by UV, 1 H-NMR and 13 C-NMR spectra by comparision with an authentic sample or the reported compound. 27,28) Statistical Analyses Data were expressed as the meanϮ S.D. The significance of difference was evaluated using Student's t-test 29) and pϽ0.05 was taken as significant.…”
Section: Isolation and Identification Of Antioxidant Componentsmentioning
confidence: 99%
“…We found that sweetpotato leaves contain large amounts of polyphenols and identified caffeic acid (CA) and five types of caffeoylquinic acid (CQA) derivatives, mono-, diand triCQAs (Islam et al, 2002). Mono-and diCQAs are ubiquitously present in plants.…”
Section: Introductionmentioning
confidence: 99%
“…11) Our previous experiments revealed that sweet potato leaves have a higher CQA content compared to other major commercial vegetables. 4) Our previous experiments also showed that the order of the anti-mutagenicity of CQAs was as follows: 3,4,5-triC-QA > diCQAs > 5-CQA. 12) About a decade ago, NARO/KARC developed "Suioh", a sweet potato cultivar, whose leaves are also edible.…”
mentioning
confidence: 82%
“…Especially, coffee beans (27.9-52.0 g kg −1 dw), eggplant plant fruits (14.1-28.0 g kg −1 dw), mate tea (4.8-24.9 g kg −1 dw), and sweet potato leaves (14.2-171 g kg −1 dw) contained high amount of CQAs. [1][2][3][4] In addition, it is estimated that humans consume up to 1.0 g of CQAs per day. 5) CQAs have several beneficial properties, and in in vitro and in vivo experiments, have been found to induce anti-oxidant, 6) anti-hyperglycemic, 7) anti-melanogenic, 8) and neuroprotective effects.…”
mentioning
confidence: 99%